2009
DOI: 10.1007/s00420-009-0440-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, job demand–control, perceived stress–energy, and salivary cortisol in white-collar workers

Abstract: Physically active employees perceive less stress and more energy. The association between stress-energy and salivary cortisol was affected by vigorous physical activity. No association between job control-demand and the degree of physical activity was found. Based on the present data, we recommend office workers-exposed to high job strain and inactivity at the job-to perform physical activity, preferably of high intensity, in order to reduce stress and increase energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 44 publications
3
46
2
Order By: Relevance
“…Physical activity was not registered in the present study, but high scores on coping were significantly related to having less SHC and fatigue, and being more physically fit. This indicates that the more healthy and coping individuals within the LBP patient group may be more physically active, which has previously shown to be reflected in higher evening values of cortisol (Hansen et al 2010). …”
Section: Discussionmentioning
confidence: 84%
“…Physical activity was not registered in the present study, but high scores on coping were significantly related to having less SHC and fatigue, and being more physically fit. This indicates that the more healthy and coping individuals within the LBP patient group may be more physically active, which has previously shown to be reflected in higher evening values of cortisol (Hansen et al 2010). …”
Section: Discussionmentioning
confidence: 84%
“…This result is supported by Aldana et al (2), who showed that working adults who participated in leisure time physieal activity had nearly half the rate of perceived stress as nonexercisers. Similarly, other studies have confirmed a positive relationship between exercise and perceived stress studied within the context of job performance and health complaints (14,25).…”
Section: Discussionmentioning
confidence: 91%
“…Stress is produced by events perceived to be uncontrollable and threatening, such that situations that place high demands on an individual when her perceptions of control are low are most likely to induce stress (Hansen et al, 2010). Thus, it is important to note that a woman's perception of her work and family roles may be a better predictor of stress than the actual number or extent of demands.…”
Section: Introductionmentioning
confidence: 99%